Preparation method of hollow fiber composite loose nanofiltration membrane

By preparing hollow fiber composite loose nanofiltration membranes, cross-linking and optimization treatment are performed using composite materials of polymers and nanoparticles, the existing hollow fiber nanofiltration membrane has low flux, low separation efficiency and poor anti-pollution performance, and high efficiency and durable nanofiltration membrane performance are achieved.

CN119633618APending Publication Date: 2025-03-18QICHENG (JIANGSU) PURIFICATION TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510070543.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-03-18
Patent Text Reader

Abstract

The invention discloses a preparation method of a hollow fiber composite loose nanofiltration membrane, which specifically comprises the following processing steps: S1, firstly preparing materials, and manufacturing a hollow fiber membrane matrix; s2, manufacturing a composite loose layer; s3, carrying out cross-linking curing treatment on the membrane; s4, carrying out optimization treatment on the membrane; and S5, testing the performance of the film. According to the invention, the polyvinyl alcohol (PVA), the polyacrylic acid (PAA), the polyvinylpyrrolidone (PVP), the silicon dioxide, the carbon nano tube and the nano metal oxide are adopted as composite materials, and the selection and combination of the materials have relatively strong innovativeness in the field of nanofiltration membranes; the synergistic effect of the polymer and the nanoparticles is beneficial for improving the hydrophilicity, the separation performance and the anti-pollution capacity of the membrane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, in particular to a method for preparing a hollow fiber composite loose nanofiltration membrane. Background Art

[0002] Hollow fiber composite loose nanofiltration membrane is a membrane technology used to separate solid particles, dissolved substances, bacteria and other substances. This membrane is usually composed of hollow fibers and loose layers, and has high filtration performance and large flux. Hollow fiber composite loose nanofiltration membrane is widely used in water treatment, wastewater treatment, food processing and other fields. The structural design of this membrane makes it have high anti-pollution ability and long service life. By adjusting the material and structure, it is possible to achieve effective separation and concentration of substances with different particle sizes and different components. This membrane technology is increasingly used in the industrial and environmental fields, and is of great significance to resource recovery and waste treatment.

[0003] Existing hollow fiber nanofiltration membranes often have problems such as low flux, low separation efficiency, and poor anti-pollution performance. Here we propose a method for preparing a hollow fiber composite loose nanofiltration membrane. Summary of the invention

[0004] In order to solve the above technical deficiencies, the present invention adopts a modified technical solution, a method for preparing a hollow fiber composite loose nanofiltration membrane, which specifically includes the following processing steps:

[0005] S1, first prepare materials and make a hollow fiber membrane matrix;

[0006] S2, making a composite loose layer;

[0007] S3, cross-linking and curing the film;

[0008] S4, optimizing the membrane;

[0009] S5, performing performance tests on the membrane.

[0010] As a further preferred embodiment of the present invention, step S1 specifically includes the following steps: first, a high molecular polymer is selected as a matrix material, including polyethersulfone (PES), polyetherketone (PEK), and polytetrafluoroethylene (PTFE); the polymer is dissolved in an appropriate organic solvent N,N-dimethylformamide (DMF) or dichloromethane (DCM) to form a polymer solution, and the concentration of the solution is controlled between 13% and 28%; the prepared polymer solution is evenly coated on a pretreated metal or plastic support tube through a casting tool to form a uniform film layer, and the coated matrix is ​​immersed in a cooling water bath for phase inversion to form a hollow fiber membrane with a loose porous structure. The temperature during the phase inversion process should be controlled between 0-35°C, and the immersion time is generally 30-60 seconds to ensure that the membrane matrix has a suitable pore structure. The pore size range of the hollow fiber membrane is 0.1-1.5 microns.

[0011] As a further preferred embodiment of the present invention, in step S2, the material includes a polymer solution and a nanoparticle mixture, the polymer solution includes 1-2 parts of polyvinyl alcohol (PVA), 2-6 parts of polyacrylic acid (PAA), and 3-6 parts of polyvinyl pyrrolidone (PVP), and the nanoparticle mixture includes 2-4 parts of silicon dioxide, 2-4 parts of carbon nanotubes, and 1-2 parts of nano metal oxides. The polymer solution and the nanoparticle mixture are dissolved in a mixture of water and ethanol in a ratio of 2:8 to form a composite coating solution, the concentration of the polymer solution is 5%-15%, and the concentration of the nanoparticles is 0.5%-3%. The hollow fiber membrane substrate is immersed in the composite coating solution, and the composite layer is evenly coated on the surface of the membrane substrate by spin coating or spraying. The thickness of the coating should be controlled between 0.1-2 microns.

[0012] As a further preferred embodiment of the present invention, in step S3, a heat crosslinking treatment is first performed to heat treat the hollow fiber membrane coated with the composite layer, and the temperature is controlled at 60-90°C for 30-75 minutes. Thermal crosslinking promotes crosslinking between polymer molecules in the coating, enhances the chemical stability and mechanical strength of the membrane, and then ultraviolet light crosslinking is performed. The ultraviolet light wavelength is usually selected between 100-250 nanometers, and the irradiation time is 5-15 minutes.

[0013] As a further preferred embodiment of the present invention, in step S4, cleaning and degreasing are first performed, and the prepared hollow fiber membrane is immersed in deionized water to remove residual solvents, unreacted chemicals and surface impurities. After cleaning, the membrane is blown dry with clean air or nitrogen, and then the pore size is adjusted and the membrane performance is optimized, using a PH6.5 HCL solution or a PH8.5 NAOH solution to obtain the target separation performance.

[0014] As a further preferred embodiment of the present invention, step S5 includes performing a water flux test, a separation performance test, and an anti-pollution performance test on the membrane. The water flux test uses a Dead-End filtration method to test the water flux of the membrane. Under an operating pressure of 1 bar, the water flux should reach 100-200 L / m 2 ·h.

[0015] As a further preferred embodiment of the present invention, the separation performance test tests the retention performance of the membrane for standard solution NaCl, glucose or protein, and nanoparticles, and evaluates the nanofiltration performance of the membrane, with a retention rate greater than 90% for the target solute.

[0016] Beneficial effects:

[0017] The present invention uses a composite material of polyvinyl alcohol (PVA), polyacrylic acid (PAA), polyvinyl pyrrolidone (PVP) and silicon dioxide, carbon nanotubes and nano metal oxides. The selection and combination of these materials are highly innovative in the field of nanofiltration membranes. The synergistic effect of polymers and nanoparticles helps to improve the hydrophilicity, separation performance and anti-pollution ability of the membrane. By finely controlling the proportion of these components, the solvent system and the coating method, the high efficiency and durability of the membrane are successfully achieved.

[0018] After the present invention adopts the composite loose layer and double cross-linking treatment technology, the membrane surface has good anti-pollution performance. Anti-pollution ability is a key bottleneck of membrane technology. The design of the composite layer enables the membrane to have strong self-cleaning properties, can effectively resist common pollutants, reduce the frequency of membrane cleaning, and increase the service life of the membrane. Enhanced membrane mechanical strength and stability: Double cross-linking thermal cross-linking and ultraviolet light cross-linking treatments significantly improve the mechanical strength and chemical stability of the membrane, especially under extreme conditions such as high temperature, high pressure and contact with chemicals. The membrane can maintain a high stability and is suitable for long-term operation and industrial applications. DETAILED DESCRIPTION

[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] The present invention provides a technical solution: a method for preparing a hollow fiber composite loose nanofiltration membrane, which specifically includes the following processing steps:

[0021] S1, first prepare materials and make a hollow fiber membrane matrix;

[0022] S2, making a composite loose layer;

[0023] S3, cross-linking and curing the film;

[0024] S4, optimizing the membrane;

[0025] S5, performing performance tests on the membrane.

[0026] Step S1 specifically includes the following steps: firstly, a high molecular polymer is selected as a matrix material, including polyethersulfone (PES), polyetherketone (PEK), polytetrafluoroethylene (PTFE), and the polymer is dissolved in an appropriate organic solvent N,N-dimethylformamide (DMF) or dichloromethane (DCM) to form a polymer solution, and the concentration of the solution is controlled between 13% and 28%;

[0027] The prepared polymer solution is evenly coated on the pretreated metal or plastic support tube through a casting tool to form a uniform film layer. The coated substrate is immersed in a cooling water bath for phase inversion to form a hollow fiber membrane with a loose porous structure. The temperature during the phase inversion process should be controlled between 0-35°C and the immersion time is generally 30-60 seconds to ensure that the membrane substrate has a suitable pore structure. The pore size range of the hollow fiber membrane is 0.1-1.5 microns.

[0028] In step S2, the material includes a polymer solution and a nanoparticle mixture, the polymer solution includes 1-2 parts of polyvinyl alcohol (PVA), 2-6 parts of polyacrylic acid (PAA), and 3-6 parts of polyvinyl pyrrolidone (PVP), and the nanoparticle mixture includes 2-4 parts of silicon dioxide, 2-4 parts of carbon nanotubes, and 1-2 parts of nano metal oxides. The polymer solution and the nanoparticle mixture are dissolved in a water and ethanol mixture in a ratio of 2:8 to form a composite coating solution. The concentration of the polymer solution is 5%-15%, and the concentration of the nanoparticles is 0.5%-3%. The hollow fiber membrane substrate is immersed in the composite coating solution, and the composite layer is evenly coated on the surface of the membrane substrate by spin coating or spraying. The thickness of the coating should be controlled between 0.1-2 microns.

[0029] Step S3, first perform heat crosslinking treatment, heat treat the hollow fiber membrane coated with the composite layer, control the temperature at 60-90°C, and the time is 30-75min. Thermal crosslinking promotes the crosslinking between polymer molecules in the coating, enhances the chemical stability and mechanical strength of the membrane, and then perform ultraviolet light crosslinking treatment by ultraviolet light irradiation crosslinking treatment. The ultraviolet light wavelength is usually selected between 100-250 nanometers, and the irradiation time is 5-15min.

[0030] In step S4, cleaning and degreasing are first performed, and the prepared hollow fiber membrane is immersed in deionized water to remove residual solvents, unreacted chemicals and surface impurities. After cleaning, the membrane is blown dry with clean air or nitrogen, and then the pore size is adjusted and the membrane performance is optimized, using a PH6.5 HCL solution or a PH8.5 NAOH solution to obtain the target separation performance.

[0031] Step S5 includes testing the membrane for water flux, separation performance, anti-fouling performance, and water flux. The dead-end filtration method is used to test the water flux of the membrane. Under an operating pressure of 1 bar, the water flux should reach 100-200 L / m 2 ·h.

[0032] Separation performance test, testing the retention performance of the membrane for standard solution NaCl, glucose or protein, nanoparticles, evaluating the nanofiltration performance of the membrane, the retention rate is greater than 90% for the target solute.

[0033] Embodiment 1

[0034] First, prepare materials to make a hollow fiber membrane matrix. First, select a high molecular polymer as the matrix material, including polyethersulfone (PES), polyetherketone (PEK), polytetrafluoroethylene (PTFE), dissolve the polymer in an appropriate organic solvent N,N-dimethylformamide (DMF) or dichloromethane (DCM) to form a polymer solution, and the concentration of the solution is controlled at 28%; the prepared polymer solution is evenly coated on a pretreated metal or plastic support tube through a casting tool to form a uniform film layer, and the coated matrix is ​​immersed in a cooling water bath for phase inversion to form a hollow fiber membrane with a loose porous structure. The temperature during the phase inversion process should be controlled at 35°C, and the immersion time is generally 60 seconds to ensure that the membrane matrix has a suitable pore structure. The pore size range of the hollow fiber membrane is 1.5 microns;

[0035] A composite loose layer is prepared, wherein the materials include a polymer solution and a nanoparticle mixture, wherein the polymer solution includes 2 parts of polyvinyl alcohol (PVA), 6 parts of polyacrylic acid (PAA), and 6 parts of polyvinyl pyrrolidone (PVP), and the nanoparticle mixture includes 4 parts of silicon dioxide, 4 parts of carbon nanotubes, and 2 parts of nano metal oxides. The polymer solution and the nanoparticle mixture are dissolved in a water-ethanol mixture at a ratio of 2:8 to form a composite coating solution, wherein the concentration of the polymer solution is 15%, and the concentration of the nanoparticles is 3%. A hollow fiber membrane substrate is immersed in the composite coating solution, and a composite layer is evenly coated on the surface of the membrane substrate by spin coating or spray coating, and the thickness of the coating should be controlled within 2 microns.

[0036] The membrane is cross-linked and cured. First, a heat cross-linking treatment is performed. The hollow fiber membrane coated with the composite layer is heat-treated at 90°C for 75 minutes. The heat cross-linking promotes the cross-linking between the polymer molecules in the coating and enhances the chemical stability and mechanical strength of the membrane. Then, ultraviolet light cross-linking is performed. The ultraviolet light wavelength is usually selected at 250 nanometers and the irradiation time is 15 minutes.

[0037] The membrane is optimized by first cleaning and degreasing. The prepared hollow fiber membrane is immersed in deionized water to remove residual solvents, unreacted chemicals and surface impurities. After cleaning, the membrane is blown dry with clean air or nitrogen. The pore size is adjusted and the membrane performance is optimized. A NAOH solution with a pH of 8.5 is used to obtain the target separation performance.

[0038] The membrane performance test includes water flux test, separation performance test, anti-fouling performance test, water flux test, using Dead-End filtration method to test the water flux of the membrane. Under 1 bar operating pressure, the water flux should reach 200L / m 2 h, separation performance test, testing the retention performance of the membrane for standard solution NaCl, glucose or protein, nanoparticles, evaluating the nanofiltration performance of the membrane, the retention rate is greater than 90% for the target solute.

[0039] Embodiment 2

[0040] First, prepare the materials to make the hollow fiber membrane matrix. First, select high molecular polymer as the matrix material, including polyethersulfone (PES), polyetherketone (PEK), polytetrafluoroethylene (PTFE), dissolve the polymer in an appropriate organic solvent N,N-dimethylformamide (DMF) or dichloromethane (DCM) to form a polymer solution, and the concentration of the solution is controlled between 13% and 28%; the prepared polymer solution is evenly coated on the pretreated metal or plastic support tube through a casting tool to form a uniform film layer, and the coated matrix is ​​immersed in a cooling water bath for phase inversion to form a hollow fiber membrane with a loose porous structure. The temperature during the phase inversion process should be controlled between 5°C, and the immersion time is generally 30 seconds to ensure that the membrane matrix has a suitable pore structure. The pore size range of the hollow fiber membrane is 0.1 micron;

[0041] A composite loose layer is prepared, wherein the materials include a polymer solution and a nanoparticle mixture, wherein the polymer solution includes 1 part of polyvinyl alcohol (PVA), 2 parts of polyacrylic acid (PAA), and 3 parts of polyvinyl pyrrolidone (PVP), and the nanoparticle mixture includes 2 parts of silicon dioxide, 2 parts of carbon nanotubes, and 1 part of nano metal oxide. The polymer solution and the nanoparticle mixture are dissolved in a water-ethanol mixture at a ratio of 2:8 to form a composite coating solution, wherein the concentration of the polymer solution is 5%, and the concentration of the nanoparticles is 0.5%. A hollow fiber membrane substrate is immersed in the composite coating solution, and a composite layer is evenly coated on the surface of the membrane substrate by spin coating or spray coating, and the thickness of the coating should be controlled to be 0.1 micrometers.

[0042] The membrane is cross-linked and cured. First, a heat cross-linking treatment is performed. The hollow fiber membrane coated with the composite layer is heat-treated at a temperature of 60°C for 30 minutes. The heat cross-linking promotes the cross-linking between the polymer molecules in the coating and enhances the chemical stability and mechanical strength of the membrane. Then, ultraviolet light cross-linking is performed. The ultraviolet light wavelength is usually selected to be 100 nanometers and the irradiation time is 5 minutes.

[0043] The membrane is optimized by first cleaning and degreasing. The prepared hollow fiber membrane is immersed in deionized water to remove residual solvents, unreacted chemicals and surface impurities. After cleaning, the membrane is blown dry with clean air or nitrogen. The pore size is adjusted and the membrane performance is optimized. A PH 6.5 HCL solution is used to obtain the target separation performance.

[0044] The membrane performance test includes water flux test, separation performance test, anti-fouling performance test, water flux test, using Dead-End filtration method to test the water flux of the membrane. Under 1 bar operating pressure, the water flux should reach 100L / m 2 h, separation performance test, testing the retention performance of the membrane for standard solution NaCl, glucose or protein, nanoparticles, evaluating the nanofiltration performance of the membrane, the retention rate is greater than 90% for the target solute.

[0045] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic features of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes that fall within the meaning and scope of the equivalent elements of the claims are included in the present invention.

[0046] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing a hollow fiber composite loose nanofiltration membrane, characterized in that: The processing steps include: S1, first prepare materials and make a hollow fiber membrane matrix; S2, making a composite loose layer; S3, cross-linking and curing the film; S4, optimizing the membrane; S5, performing performance tests on the membrane.

2. The method for preparing a hollow fiber composite loose nanofiltration membrane according to claim 1, characterized in that: Step S1 specifically includes the following steps: first, a high molecular polymer is selected as a matrix material, including polyethersulfone (PES), polyetherketone (PEK), and polytetrafluoroethylene (PTFE); the polymer is dissolved in an appropriate organic solvent N,N-dimethylformamide (DMF) or dichloromethane (DCM) to form a polymer solution, and the concentration of the solution is controlled between 13% and 28%; the prepared polymer solution is evenly coated on a pretreated metal or plastic support tube through a casting tool to form a uniform film layer, and the coated matrix is ​​immersed in a cooling water bath for phase inversion to form a hollow fiber membrane with a loose porous structure. The temperature during the phase inversion process should be controlled between 0-35°C, and the immersion time is generally 30-60 seconds to ensure that the membrane matrix has a suitable pore structure. The pore size range of the hollow fiber membrane is 0.1-1.5 microns.

3. The method for preparing a hollow fiber composite loose nanofiltration membrane according to claim 2, characterized in that: In step S2, the material includes a polymer solution and a nanoparticle mixture, the polymer solution includes 1-2 parts of polyvinyl alcohol (PVA), 2-6 parts of polyacrylic acid (PAA), and 3-6 parts of polyvinyl pyrrolidone (PVP), and the nanoparticle mixture includes 2-4 parts of silicon dioxide, 2-4 parts of carbon nanotubes, and 1-2 parts of nano metal oxides. The polymer solution and the nanoparticle mixture are dissolved in a water and ethanol mixture in a ratio of 2:8 to form a composite coating solution, the concentration of the polymer solution is 5%-15%, and the concentration of the nanoparticles is 0.5%-3%. The hollow fiber membrane substrate is immersed in the composite coating solution, and the composite layer is evenly coated on the surface of the membrane substrate by spin coating or spraying. The thickness of the coating should be controlled between 0.1-2 microns.

4. The method for preparing a hollow fiber composite loose nanofiltration membrane according to claim 3, characterized in that: Step S3, first perform heat crosslinking treatment, heat treat the hollow fiber membrane coated with the composite layer, control the temperature at 60-90°C, and the time is 30-75min. Thermal crosslinking promotes the crosslinking between polymer molecules in the coating, enhances the chemical stability and mechanical strength of the membrane, and then perform ultraviolet light crosslinking treatment by ultraviolet light irradiation crosslinking treatment. The ultraviolet light wavelength is usually selected between 100-250 nanometers, and the irradiation time is 5-15min.

5. The method for preparing a hollow fiber composite loose nanofiltration membrane according to claim 4, characterized in that: In step S4, cleaning and degreasing are first performed, and the prepared hollow fiber membrane is immersed in deionized water to remove residual solvents, unreacted chemicals and surface impurities. After cleaning, the membrane is blown dry with clean air or nitrogen, and then the pore size is adjusted and the membrane performance is optimized, using a PH6.5 HCL solution or a PH8.5 NAOH solution to obtain the target separation performance.

6. The method for preparing a hollow fiber composite loose nanofiltration membrane according to claim 5, characterized in that: Step S5 includes testing the membrane for water flux, separation performance, and anti-fouling performance. The water flux test uses the Dead-End filtration method to test the water flux of the membrane. Under an operating pressure of 1 bar, the water flux should reach 100-200 L / m 2 ·h.

7. The method for preparing a hollow fiber composite loose nanofiltration membrane according to claim 6, characterized in that: The separation performance test tests the retention performance of the membrane for standard solution NaCl, glucose or protein, and nanoparticles, and evaluates the nanofiltration performance of the membrane. The retention rate is greater than 90% for the target solute.